Assessing the cost-effectiveness of contraceptive methods from a health provider perspective: case study of Kiambu County Hospital, Kenya - James Kiragu Ngacha; Richard Ayah (BMC, 2022)
Plain language summary The proportion of women of reproductive age using a contraceptive method in Kenya, at 53% is low. More funding is required to ensure women who need contraceptives have access and continue using them. Previous research has shown that contraceptives that protect a woman from getting pregnant for an extended period utilize less resources. This study assessed the potential of contraceptives used in Kenya to produce results at less cost. This study was undertaken in a sub-national referral hospital in mid-2018. A sample of 5 family planning clinic providers were interviewed while 15 contraceptive service sessions per method were observed. The interviews were conducted to determine the supplies required to offer services. Observation was used to measure time taken to provide each contraceptive method. The cost associated with providing each contraceptive per year was determined using activity based costing. Effectiveness of each method was determined using the rate of protection from pregnancy during one-year. Cost-effectiveness was the money utilized to achieve protection from pregnancy in one year of use. The Copper-T coil was found to achieve greater results at a lesser cost of 4.87 US dollars for one year of protection from pregnancy, followed by the 2-Rod Implant at US dollars 6.36, the 1-Rod Implant at 9.50, DMPA at 23.68, and The Pill at 38.60 US dollars. Contraceptive methods that protect a woman from getting pregnant for a longer period utilize less resources. Investing in such would save costs despite requiring higher initial cost of service provision.